A Mo-doped TiNb2O7 anode for lithium-ion batteries with high rate capability due to charge redistribution1. Issue 48 (18th June 2015) - Song, Hannah; Kim, Yong-Tae
<x xml:space="preserve">Abstract</x> High rate capability of TiNb2O7 due to charge redistribution upon doping with Mo6+.